Metapatologi Abraham Maslow Menurut Perspektif Al-Quran - Ina Zainah Nasution (Al-Ulum: Jurnal Pendidikan Islam, 2020)
The hierarchical theory of multilevel needs, which was initiated by Abraham Maslow as the founder of Humanistic Psychology, is not yet fully understood. Above the need for self-actualization which occupies the last rung of the basic needs theory, Abraham Maslow stated his concept of metaneeds as the highest need. The theory of high needs (metaneeds) is an abstract need of the human soul which means being above the need for self-actualization. The concept of high needs is not as popular as the concept of basic needs. It even seems forgotten. This is because the Western view which is rooted in materialistic philosophy requires science to be in the empirical realm (sensory experience) and rejects belief in transcendental and unseen things. This is what makes the final concept of human needs initiated by Abraham Maslow like hanging and stopping until the concept of self-actualization alone. Therefore, it can be said that metaneeds (high needs, spiritual needs) are the missing rung in the unified whole concept of Abraham Maslow's ideas about motives and motivation. Maslow's metaneeds include truth, unity, harmony, justice, self-autonomy (independence), uniqueness, kindness, ease, simplicity, joy, and meaning in life in values (religion). If the need for things that are noble and abstract is not fulfilled, it can lead to metapatology or mental illness which in the language of the Koran is known as mental illness which has an impact on hardness and harshness of the heart. Keywords: Abraham Maslow, metaneeds, metapathology, humanistic psychology